2009
DOI: 10.2353/ajpath.2009.080079
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin-Radixin-Moesin-Binding Phosphoprotein (EBP50), an Estrogen-Inducible Scaffold Protein, Contributes to Biliary Epithelial Cell Proliferation

Abstract: Ezrin-radixin-moesin-binding phosphoprotein 50 (EBP50) anchors and regulates apical membrane proteins in epithelia. EBP50 is inducible by estrogen and may affect cell proliferation, although this latter function remains unclear. The goal of this study was to determine whether EBP50 was implicated in the ductular reaction that occurs in liver disease. EBP50 expression was examined in normal human liver, in human cholangiopathies (ie, cystic fibrosis, primary biliary cirrhosis, and primary sclerosing cholangitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…They found that EBP50 overexpression is significantly associated with tumor stage, metastatic progression, poor prognosis and ER status (5,9). The expression and distribution of EBP50 are regulated by estrogens and contribute to the proliferative response in biliary epithelial cells (10). We discovered that EBP50 is a novel marker for gastric adenocarcinoma and is involved in the proliferation, migration, and invasion of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 92%
“…They found that EBP50 overexpression is significantly associated with tumor stage, metastatic progression, poor prognosis and ER status (5,9). The expression and distribution of EBP50 are regulated by estrogens and contribute to the proliferative response in biliary epithelial cells (10). We discovered that EBP50 is a novel marker for gastric adenocarcinoma and is involved in the proliferation, migration, and invasion of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 92%
“…The up-regulation of EBP50 has been reported in multiple disease states including hepatocellular carcinomas, cholangiopathies, glioblastoma, breast cancer, psoriasis, and vascular injury (21,(32)(33)(34)(35)(36)(37). However, little is known about the transcriptional regulation of EBP50 expression in normal and disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time reverse transcription-polymerase chain reaction (RT-PCR) was performed as described previously (Fouassier et al, 2009). Briefly, total RNA was extracted from cultured cells and used for reverse transcription with 200 U of Moloney murine leukemia virus reverse transcriptase (Invitrogen) for 1 h at 37 1C.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Immunofluorescence Immunofluorescence was performed as described previously (Fouassier et al, 2009). Briefly, cells were fixed in 4% paraformaldehyde for 15 min, permeabilized in 0.1% SurfactAmps X100 (Thermo Scientific, Rockford, IL, USA) for 10 min and blocked with 1% albumin and 10% goat serum for 1 h at room temperature.…”
Section: Immunoprecipitation and Immunoblotmentioning
confidence: 99%
See 1 more Smart Citation